Pendekatan Pedagogis dalam Pengajaran Hadis di Era Pendidikan Islam Kontemporer - Hafid, Saidah; Tasbih (Al-Ulum, 2025)
This study explores the effectiveness of innovative pedagogical approaches in hadith instruction at Athirah 2 Islamic School Makassar. The research focuses on how interactive methods, technological integration, and contextual approaches enhance students’ comprehension, participation, and motivation in internalizing hadith values. Employing a qualitative case study design, data were collected through semi-structured interviews and classroom observations, and analyzed using thematic techniques to identify key patterns and themes. The findings reveal that the use of learning technologies, group discussions, and contextual material development significantly strengthen student engagement and the relevance of hadith to everyday life. The contribution of this research lies in proposing a new pedagogical model that integrates cognitive, moral, and spiritual dimensions, while also highlighting challenges such as human resource limitations and teacher readiness as critical factors in implementation.